An aging India : perspectives, prospects, and policies - Liebig, Phoebe S.; Rajan, S. Irudaya (Sebastian Irudaya), 1959- (New York : Haworth Press ; Routledge, 2015)
Explore Indian policy and practice on aging from a variety of perspectives! This pathbreaking collection provides something that has been missing in the literature on aging in India, especially for non-Indian audiences: studies of various aspects of aging in India combined with analyses of current policies, policy trends and recommendations. You'll examine aging issues from a variety of perspectives?demographic foundations, social and family relations, economics, health and disability, current interventions, and advocacy and policy. An Aging India also provides you with up-to-date ref.
Table of Contents; Acknowledgments; Introduction; An Aging India: Perspectives, Prospects, and Policies; Foundations of Aging in India; Demography of Indian Aging, 2001-2051; Perspectives of Research on Aging in India; Economics, Health, and Social Networks; Economic Security for the Elderly in India: An Overview; Health Status and Health Care Services Among Older Persons in India; Aging, Disability, and Disabled Older People in India; Social and Familial Relations. Social Networks of Old People in India: Research and PolicyIssues of Elder Care and Elder Abuse in the Indian Context; Current Interventions; Geriatric Hospitals in India, Today and in the Future; Old-Age Homes and Services: Old and New Approaches to Aged Care; The Role of Non-Governmental Organizations for the Welfare of the Elderly: The Case of HelpAge India; Advocacy and Policy; Senior Grassroots Organizations in India; Towards a Policy for Aging in India; Index.
"Co-published simultaneously as Journal of aging & social policy, volume 15, numbers 2/3 2003."
Includes bibliographical references and index.
ESS
Karim International
Keywords: Aging -- India; Older people -- Government policy -- India; Older people -- Services for -- India; Older people -- India; Older people -- India; Public Policy -- India; Economics